2010
DOI: 10.1016/j.vacuum.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between thermal properties and aluminum fractions in CrAlN layers deposited by PVD technique

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. The CrAlN coatings are a good alternative to conventional CrN coatings especially for high temperature oxidation-resistance applications. Different CrAlN coatings were deposited on silicon (100) by PVD (Physical vapor deposition) technique from two targets (chromium and aluminum) in a reactive nitrogen atmosphere at aluminum applied negative voltage (À300, À500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The highly mobile adatoms can move or diffuse into the inter-grain voids under the high energy ion bombardment, break down the large columnar grain growth. Therefore, a denser structure was attained [22]. As the wear failure for CrN1 sliding in seawater environment was demonstrated to occur at the interface between coating and substrate, Cr was chosen as an interlayer to improve the anti-wear property of CrN coatings under this environmental.…”
Section: Influence Of Coating Density and Interlayer On The Wear Of Cmentioning
confidence: 99%
“…The highly mobile adatoms can move or diffuse into the inter-grain voids under the high energy ion bombardment, break down the large columnar grain growth. Therefore, a denser structure was attained [22]. As the wear failure for CrN1 sliding in seawater environment was demonstrated to occur at the interface between coating and substrate, Cr was chosen as an interlayer to improve the anti-wear property of CrN coatings under this environmental.…”
Section: Influence Of Coating Density and Interlayer On The Wear Of Cmentioning
confidence: 99%
“…It has been reported that the Al 2 O 3 phase is more thermally stable and protective than the Cr 2 O 3 phase at high temperatures [7][8][9]. Because of these benefits, the CrAlN coating is considered as a good alternative to the conventional coatings especially for the high temperature oxidation-resistance applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that all the Cr 1−x Al x N films demonstrate B1‐type crystal structure, suggesting that the crystalline structure of the Cr 1−x Al x N films is similar to that of CrN film. As the Al content increases from 0 to 0.84, the diffraction angle shifts toward higher 2 θ angle, which can be ascribed to the substitution of some of the Cr atoms by smaller Al atoms in CrN lattice . Moreover, the increase of strong Al‐N bond results in the contraction of the CrN lattice.…”
Section: Resultsmentioning
confidence: 97%